Efektivitas Kombinasi Ekstrak Bunga Telang (Clitoria ternatea L.) dan Daun Kelor (Moringa oleifera) Terhadap Bakteri Escherichia Coli dalam Sediaan Gel Hand Sanitizer - Ariza, Angga Dwi; Ulfa , Ade Maria; Chusniasih, Dewi (Universitas Pahlawan Tuanku Tambusai, 2025)
Butterfly pea blossoms (Clitoria ternatea L.) and Moringa leaves (Moringa oleifera) are purported to possess antibacterial properties. The antibacterial effectiveness is attributed to the potent active chemicals it possesses. One of the topical antibacterial agents is gel. Gel is a semi-solid formulation including colloids intended for external application. This research seeks to ascertain the feasibility of formulating a hand sanitizer gel utilizing a combination of butterfly pea flower extract and Moringa leaves, as well as to evaluate the antibacterial efficacy of this gel preparation against the proliferation of Escherichia coli bacteria. This research employed the maceration process utilizing a 96% ethanol solvent for extraction. The utilized extract concentrations are 1:1, 1:2, and 2:1. Each concentration of the gel formulation underwent a physical evaluation, followed by an efficacy assessment against Escherichia coli germs via the well diffusion method. The data were examined utilizing a one-way ANOVA test. The research findings indicate that the amalgamation of butterfly pea flower extract and Moringa leaves is suitable for hand sanitizer gel formulations, with formulations II and III receiving favorable evaluations. In the antibacterial efficacy test, formulation II demonstrated significant results with an average inhibition zone of 14.167 mm.